Kompetensi Kepribadian, Sosial Dan Profesional Terhadap Peningkatan Kinerja Guru di SMK Al Khoiriyah - Mukarromah, Niswatul; Arisyahidin, Arisyahidin; Talkah, Abu; Baehaki, Imam (Universitas Islam Kadiri, 2025)
This study aims to determine and analyze the influence of personality, social and professional competencies on improving teacher performance at SMK Al Khoiriyah. This study uses a quantitative approach with an associative design. The sampling technique used is saturated sampling method, involving all teachers at SMK Al Khoiriyah totaling 37 respondents. Data were collected using a questionnaire. The data analysis technique used is multiple linear regression analysis using SPSS version 20,0 program. The results indicate that all three competencies positively influence teacher performance improvement, both simultaneously and partially. Teachers’ personality competence contributes to shaping professional attitudes in dealing with students and the school environment. Social competence has been proven to enhance communication effectiveness and teachers’ collaboration with various parties, which ultimately have a positive impact on the learning process. Professional competence plays an important role in increasing the effectiveness of delivering material and implementing innovative learning strategies. This finding confirms that improving teacher performance must be done comprehensively by balancing the three competencies. Therefore, it is recommended that schools continue to support the development of teacher competence through training, self-reflection and strengthening the professional community.